Justificativas para o ensino de Astronomia: o que dizem os pesquisadores brasileiros? - Langhi, Rodolfo [UNESP]; Nardi, Roberto [UNESP] (My University, 2014)
We present here a qualitative analysis of a sample of papers published in Brazilian science education journals, which expresses researchers discourses related to Astronomy Education. Within this analytical universe, we sought for discursive excerpts about their justifications for the teaching of this subject, which made the basis for the production of a collective discourse, which identity is socially represented by the researchers authors set. Setting up articulations with discourse analysis, the procedures of the collective subject discourse show to be an important methodological tool to answer to the central question of this study: what do the Brazilian researchers assert as justifications for teaching Astronomy? In other words: why teach Astronomy? Outcomes point to the retaking of reflections about the importance of matters like as Astronomy in formal education, catalyzing teachers work innovative articulations.

Apresentamos uma análise qualitativa de uma amostra de artigos publicados em revistas científicas brasileiras da área de Ensino, os quais expressam discursos dos pesquisadores em relação à Educação em Astronomia. Dentro do universo analítico, procuramos excertos discursivos específicos sobre as justificativas para o ensino deste tema, os quais formaram a base para a produção de um Discurso do Sujeito Coletivo, cuja identidade é representada socialmente pelo conjunto dos pesquisadores autores. Estabelecendo articulações com a Análise do Discurso, os procedimentos do Discurso do Sujeito Coletivo mostraram-se como um importante instrumento metodológico para se responder à questão central deste estudo: o que o pesquisador brasileiro afirma como justificativas para o ensino da Astronomia? Em outras palavras, buscamos responder: por que ensinar Astronomia? Os resultados apontam para a retomada de reflexões sobre a importância da abordagem de temas como a Astronomia na educação formal, catalisando articulações inovadoras do trabalho docente.
Justifications for teaching Astronomy: what do the Brazilian researchers say?
Keywords: Astronomy education; Social representations theory; Collective subject discourse; Discourse analysis; Astronomy teaching justifications; Educação em Astronomia; Teoria das representações sociais; Discurso do sujeito coletivo; Análise do discurso; Justificativas para o ensino da Astronomia